Comparison of diabetic and non-diabetic human leukocytic responses to different capsule types of klebsiella pneumoniae responsible for causing pyogenic liver abscess - Lee, I. Russel (2018)
The major risk factor for Klebsiella liver abscess (KLA) is type 2 diabetes mellitus (DM), but the immunological mechanisms involved in the increased susceptibility are poorly defined. We investigated the responses of neutrophils and peripheral blood mononuclear cells (PBMCs) to hypervirulent Klebsiella pneumoniae (hvKP), the causative agent of KLA. DNA and myeloperoxidase levels were elevated in the plasma of KLA patients compared to uninfected individuals indicating neutrophil activation, but diabetic status had no effect on these neutrophil extracellular trap (NET) biomarkers in both subject groups. Clinical hvKP isolates universally stimulated KLA patient neutrophils to produce NETs ex vivo, regardless of host diabetic status. Ability of representative capsule types (K1, K2, and non-K1/K2 strains) to survive intra- and extra-cellular killing by type 2 DM and healthy neutrophils was subsequently examined. Key findings were: (1) type 2 DM and healthy neutrophils exhibited comparable total, phagocytic, and NETs killing against hvKP, (2) phagocytic and NETs killing were equally effective against hvKP, and (3) hypermucoviscous K1 and K2 strains were more resistant to total, phagocytic, and NETs killing compared to the non-mucoviscous, non-K1/K2 strain. The cytokine response and intracellular killing ability of type 2 DM as well as healthy PBMCs upon encounter with the different capsule types was also examined. Notably, the IL-12–IFNγ axis and its downstream chemokines MIG, IP-10, and RANTES were produced at slightly lower levels by type 2 DM PBMCs than healthy PBMCs in response to representative K1 and non-K1/K2 strains. Furthermore, type 2 DM PBMCs have a mild defect in its ability to control hvKP replication relative to healthy PBMCs. In summary, our work demonstrates that type 2 DM does not overtly impact neutrophil intra- and extra-cellular killing of hvKP, but may influence cytokine/chemokine production and intracellular killing by PBMCs.